A Study of Cleaner Production and Eco-Efficiency Uptake within Western Australian Small Medium-Sized Enterprises, with a Specific Focus on Air Emissions and Related Air Quality - Latunij, Ferdinand (Curtin University, 2016)
This thesis examined the uptake of Cleaner Production and Eco-Efficiency within Western Australian Small-Medium Industries, with a specific focus on Air Emissions. It was found that, given the lack of governmental supporting and the low value of most air emissions, the CP methodology is ineffective as a means of minimising the release of low value air emissions (or emissions generated from low value product). It was therefore concluded that a holistic approach is required.